Insight into the mechanism of polyphenols on the activity of HMGR by molecular docking - Islam B; Sharma C; Adem A; Aburawi EH; Ojha S (Dove Medical Press, 2015)
Barira Islam,1,* Charu Sharma,2,* Abdu Adem,3 Elhadi Aburawi,1 Shreesh Ojha3 1Department of Paediatrics, 2Department of Internal Medicine, 3Department of Pharmacology and Therapeutics, College of Medicine and Health Sciences, United Arab Emirates University, Al-Ain, Abu Dhabi, United Arab Emirates *These authors contributed equally to this work Abstract: Statins are hypolipidemic drugs that are effective in the treatment of hypercholesterolemia by attenuating cholesterol synthesis in the liver via competitive inhibition of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase. Recently, dietary changes associated with drug therapy have garnered attention as novel drugs to mitigate or ameliorate hypercholesterolemia. The present study was undertaken to observe different dietary polyphenols that can bind to the active site of HMGR and inhibit it. Results from the 12 dietary polyphenols tested reveal that polyphenols can bind to HMGR and block the binding of nicotinamide adenine dinucleotide phosphate (NADP+). We observed that the rigidity of phenolic rings prevents the polyphenols from docking to the enzyme activity site. The presence of an ester linkage between the phenolic rings in (–)-epigallocatechin-3-gallate (EGCG) and the alkyl chain in curcumin allows them to orient in the active site of the HMGR and bind to the catalytic residues. EGCG and curcumin showed binding to the active site residues with a low GRID score, which may be a potential inhibitor of HMGR. Kaempferol showed binding to HMG-CoA, but with low binding affinity. These observations provide a rationale for the consistent hypolipidemic effect of EGCG and curcumin, which has been previously reported in several epidemiological and animal studies. Therefore, this study substantiates the mechanism of polyphenols on the activity of HMGR by molecular docking and provides the impetus for drug design involving further structure–function relationship studies. Keywords: polyphenols, HMG-CoA, EGCG, curcumin, docking, in silico